2013
DOI: 10.1002/pd.4190
|View full text |Cite
|
Sign up to set email alerts
|

Does website‐based information add any value in counseling mothers expecting a baby with severe congenital diaphragmatic hernia?

Abstract: Complementing prenatal counseling on CDH and FETO by standardized information via website is perceived by parents as of added value. Maternal risks and the need for fetal medication need more clarification during the verbal counseling prior to prenatal interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…All mothers ( n = 24) were able to accurately recall the location of the anomaly and most ( n = 22; 92%) correctly recalled the severity of the anomaly, however, fewer mothers could recall the prognosis ( n = 12; 80%) or cause ( n = 10; 56%). A more recent study found that information recall was improved by provision of a website containing relevant information . In contrast, the RCT conducted by Cope et al .…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…All mothers ( n = 24) were able to accurately recall the location of the anomaly and most ( n = 22; 92%) correctly recalled the severity of the anomaly, however, fewer mothers could recall the prognosis ( n = 12; 80%) or cause ( n = 10; 56%). A more recent study found that information recall was improved by provision of a website containing relevant information . In contrast, the RCT conducted by Cope et al .…”
Section: Resultsmentioning
confidence: 86%
“…A more recent study found that information recall was improved by provision of a website containing relevant information. 25 In contrast, the RCT conducted by Cope et al did not find any improvement in recall after providing supporting information, despite the reported reduction in parental anxiety. 18…”
Section: Impact Of Prenatal Counselling On Parental Knowledge and Recallmentioning
confidence: 88%
See 1 more Smart Citation
“…For FETO, we explicitly discussed the experimental nature of the procedure as well as the logistic implications of a fetus with an occluded trachea as described in the patient information section of the TOTAL‐trial website (http://www.totaltrial.eu). Fetuses eligible for FETO had an O/E LHR <25 or <45% for left or right sided CDH, respectively, liver herniation, a normal karyotype and no associated severe anomalies. However, fetuses with hydrops, an associated congenital pulmonary airway malformation (CPAM) or a bronchopulmonary sequestration (BPS) were still considered for FETO as these anomalies do not necessarily impact on outcome .…”
Section: Methodsmentioning
confidence: 99%
“…In a digital age, patients increasingly need digital information provision and even digital counselling . Previous studies show that websites provide added value beyond face‐to‐face information and recommend online resources . Yet they also show that it is difficult and confusing to find information online .…”
Section: Introductionmentioning
confidence: 99%